Learning history through web scraping and Tableau public: Is it possible? - Joko Ade Nursiyono; Peni Meivita (Universitas Muhammadiyah Malang, 2022)
Learning history has a central role in cultivating patriotism and nationalism value for students. Various countries have placed historical education as a crucial part of national education. It is due to the belief that historical education materials can develop the nature and character of the nation's young generation. Technological developments make it easier for us to create innovative media, such as web scraping. Learning history with proper media can foster students' motivation to understand the content, such as the names and roles of national heroes. Web scraping is used to collect data from sites related to 60 national heroes and their places of birth. The data is then processed and visualized in Tableau Public. The result shows that the learning media can be categorized as good (53%). The respondent stated that the history learning media is very useful (67%). Meanwhile, regarding the effectiveness of the linkage feature between the data in the visualization, all respondents stated is good.